DNTT activation, TdT‐aided gene length mutation, and better prognosis in ATG‐based regimen allo‐HSCT in AML. Issue 5 (8th February 2023) - Zhou, Xiaosu; Nie, Daijing; Zhang, Yang; Liu, Zhixiu; Zhao, Yanli; Zhang, Jianping; Wang, Fang; Fang, Jiancheng; Cao, Panxiang; Chen, Xue; Ma, Xiaoli; Yuan, Lili; et al.
Abstract: This study aimed to investigate the relationship between anomalous DNA nucleotidylexotransferase ( DNTT ) activation and the mutagenesis of gene length mutations (LMs) in acute myeloid leukemia (AML), and the relevance of their prognosis in antithymocyte globulin (ATG)‐based regimen allogeneic hematopoietic stem cell transplantation (allo‐HSCT). A cohort of 578 AML cases was enrolled. Next‐generation sequencing was performed to screen mutations of 86 leukemia driver genes. RNA‐seq was used to analyze gene expression. Prognostic analysis was investigated in 239 AML cases who underwent ATG‐based regimen allo‐HSCT. We report a refined subtyping algorithm of LMs (type I–IV) based on sequence anatomy considering the TdT‐aided mutagenesis mechanism. GC content adjacent to LM junctions, inserted nontemplate nucleotide bases, and DNTT expression analysis supported the DNTT activation and TdT‐aided mutagenesis in type II/III LMs in the total AML cohort. Both single‐variate and multivariate analyses showed a better overall survival of FLT3 type III compared to type I in a subset of ATG‐based regimen allo‐HSCT cases. The novel LM subtyping algorithm not only deciphers the etiology of the mutagenesis of LMs but also helps to fine‐tune prognosis differentiation in AML. The possible prognostic versatility of this novel LM subtyping algorithm in terms of chemotherapy, targeted therapy, and allo‐HSCT merits further investigation.